2021
DOI: 10.3390/ijms22115686
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Behavioral Variability of Medaka Fish Assessed by Comparative Phenomics

Abstract: Recently, medaka has been used as a model organism in various research fields. However, even though it possesses several advantages over zebrafish, fewer studies were done in medaka compared to zebrafish, especially with regard to its behavior. Thus, to provide more information regarding its behavior and to demonstrate the behavioral differences between several species of medaka, we compared the behavioral performance and biomarker expression in the brain between four medaka fishes, Oryzias latipes, Oryzias da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…In this study, we investigated killifish behavior over their adult lifespan in an open field and novel tank diving test to set a baseline for future behavioral experiments. The open field test and the novel tank diving test have been widely used by zebrafish and medaka researchers in the last decade ( Egan et al, 2009 ; Cachat et al, 2010 ; Matsunaga and Watanabe, 2010 ; Rosemberg et al, 2011 ; Godwin et al, 2012 ; Stewart et al, 2012 , 2014 ; Liu et al, 2018 ; Lucon-Xiccato et al, 2020 , 2022 ; Audira et al, 2021 ). Since killifish are fast-aging, it is important to investigate behavioral changes over their adult lifespan, as this might influence experiments where the effect of a certain drug on behavior over different ages is studied ( Thoré et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we investigated killifish behavior over their adult lifespan in an open field and novel tank diving test to set a baseline for future behavioral experiments. The open field test and the novel tank diving test have been widely used by zebrafish and medaka researchers in the last decade ( Egan et al, 2009 ; Cachat et al, 2010 ; Matsunaga and Watanabe, 2010 ; Rosemberg et al, 2011 ; Godwin et al, 2012 ; Stewart et al, 2012 , 2014 ; Liu et al, 2018 ; Lucon-Xiccato et al, 2020 , 2022 ; Audira et al, 2021 ). Since killifish are fast-aging, it is important to investigate behavioral changes over their adult lifespan, as this might influence experiments where the effect of a certain drug on behavior over different ages is studied ( Thoré et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The novel tank diving test typically studies exploration, diving, and immobility/freezing behavior ( Blaser and Rosemberg, 2012 ; DePasquale et al, 2022 ). Different teleost species display different behaviors in these types of behavioral tests ( Egan et al, 2009 ; Cachat et al, 2010 ; Matsunaga and Watanabe, 2010 ; Godwin et al, 2012 ; Audira et al, 2021 ; DePasquale et al, 2022 ; Lucon-Xiccato et al, 2022 ; Saiz et al, 2023 ). In this study, we, therefore, tested the new aging model organism N. furzeri in the open field test and the novel tank diving test over its adult lifespan to set a baseline for future behavior experiments.…”
Section: Introductionmentioning
confidence: 99%
“…While serotonin is synthesised from Trp in a whole range of species and performs important functions in many physiological processes, including mood in humans, 148 aggression in vervet monkey, 87 injurious behaviour in pigeon, hens and parrots 150 or catecholamines metabolism in rats, 149 surprisingly little comparative studies of serotonin pathway activity across species or strains thereof have been reported and these are mainly concerned with response of the pathway to manipulations, such as stress. 261 alterations in dietary Trp, 262 monoamine transporters in humans, rats and mice, 263 behavioural variability in Medaka fish strains 264 and mouse strain differences in serotonin-specific reuptake inhibitor sensitivity. 265 Table 6 summarises data published on species content of brain Trp and its 5-hydroxyindole metabolites 5-HT and Cichlid (6) All values are in µM.…”
Section: Species Differences In the Serotonin Pathwaymentioning
confidence: 99%
“…We used the mirror test to assess zebrafish aggressiveness (Audira et al, 2021). The zebrafish were introduced to a rectangular tank (24.5 cm length × 14.5 cm height × 7.5 cm width) filled with 1.5 L of home tank water, with a mirror fixed to the vertical side wall.…”
Section: Mirror Testmentioning
confidence: 99%